Inventarisasi Cagar Budaya Kampung Adat Tiwutewa di Kabupaten Ende - Lay, Maria Marlince; Wati, Fatma; Bhae, Benediktus Yoseph; Wolo, Daniel (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Tiwutewa Village, about 16 km east of Ende City, has several objects that have the potential as cultural heritage. The purpose of this activity is to record objects that are suspected to have the potential to be cultural heritage objects. The method used is library research, observation and interviews. The results obtained, there are three objects that are suspected of being cultural heritage objects, namely: Tubumusu Oranata, Keda and Traditional Houses. These three objects are located precisely in the village of Kurumboro. In appearance the condition of these three objects is still well maintained because of the presence of the Mosalaki who have the task of guarding these sites. In addition, every year there are always traditional rituals centered on the three sites.